Paralog-specific TTC30 regulation of Sonic hedgehog signaling - Felix Hoffmann; Sylvia Bolz; Katrin Junger; Franziska Klose; Isabel F. Stehle; Marius Ueffing; Karsten Boldt; Tina Beyer (Frontiers in Molecular Biosciences, 2023)
The intraflagellar transport (IFT) machinery is essential for cilia assembly, maintenance, and trans-localization of signaling proteins. The IFT machinery consists of two large multiprotein complexes, one of which is the IFT-B. TTC30A and TTC30B are integral components of this complex and were previously shown to have redundant functions in the context of IFT, preventing the disruption of IFT-B and, thus, having a severe ciliogenesis defect upon loss of one paralog. In this study, we re-analyzed the paralog-specific protein complexes and discovered a potential involvement of TTC30A or TTC30B in ciliary signaling. Specifically, we investigated a TTC30A-specific interaction with protein kinase A catalytic subunit α, a negative regulator of Sonic hedgehog (Shh) signaling. Defects in this ciliary signaling pathway are often correlated to synpolydactyly, which, intriguingly, is also linked to a rare TTC30 variant. For an in-depth analysis of this unique interaction and the influence on Shh, TTC30A or B single- and double-knockout hTERT-RPE1 were employed, as well as rescue cells harboring wildtype TTC30 or the corresponding mutation. We could show that mutant TTC30A inhibits the ciliary localization of Smoothened. This observed effect is independent of Patched1 but associated with a distinct phosphorylated PKA substrate accumulation upon treatment with forskolin. This rather prominent phenotype was attenuated in mutant TTC30B. Mass spectrometry analysis of wildtype versus mutated TTC30A or TTC30B uncovered differences in protein complex patterns and identified an impaired TTC30A–IFT57 interaction as the possible link leading to synpolydactyly. We could observe no impact on cilia assembly, leading to the hypothesis that a slight decrease in IFT-B binding can be compensated, but mild phenotypes, like synpolydactyly, can be induced by subtle signaling changes. Our systematic approach revealed the paralog-specific influence of TTC30A KO and mutated TTC30A on the activity of PRKACA and the uptake of Smoothened into the cilium, resulting in a downregulation of Shh. This downregulation, combined with interactome alterations, suggests a potential mechanism of how mutant TTC30A is linked to synpolydactyly.